(untitled) (Panacea Journal of Medical Sciences, 2019)
Haemorrhoid is a common anorectal disorder which usually requires surgical intervention. Conventional haemorrhoidectomy had been practiced for long time but in 1993 Longo introduced a newer minimally invasive procedure for haemorrhoids. In this study we have compared the post-operative results of MIPH with conventional open haemorrhoidectomy. To analyze and compare various Pre and post-operative factors such as duration of surgery, post-operative pain and analgesia, duration of hospital stay, post- operative complications, recurrence and early return to work in the patients suffering from Grade III and IV Haemorrhoids undergoing Open Miligan-Morgan’s haemorrhoidectomy and Minimal Invasive Procedure for Haemorrhoids(MIPH). In this prospective study a total of sixty patients underwent surgery for grade III and IV haemorrhoids at Santosh Medical College and Hospital, Ghaziabad from April 2017 to October 2018. Thirty patients in group A underwent Milligan Morgan technique of open haemorrhoidectomy and thirty patients in group Bunderwent Longo’s technique of MIPH (Minimal Invasive Procedure for Haemorrhoids). The average duration of surgery was significantly less in MIPH group as compared to open haemorrhoidectomy group. Only 6.6% of MIPH developed early post-operative complications whereas atleast 25% of open haemorrhoidectomy developed early complications such as pain, bleeding per rectum and wound infection. Early return to work was significantly better in MIPH group. MIPH is safe with a low recurrence rate and complications. It is a nobel technique and has emerged as an alternative to open haemorrhoidectomy. Only limitation is the cost of the MIPH stapler device.